AI and Custom Marketing for Cultural Initiatives in Regional Projects: Perspectives on the Territorial Integration of Communities with Tourism - Mariflora Caruso; Laura Leopardi; Saverio Giulio Malatesta (Proceedings)
This poster delves into the integration of Artificial Intelligence (AI) with both the marketing and cultural heritage realms. By examining case studies, we elucidate AI’s pivotal role in personalizing consumer experiences within marketing. In the domain of cultural heritage, AI is instrumental in crafting bespoke experiences, such as the “Hermes—a trip as you like it” project. By utilizing AI algorithms, this initiative tailors customized itineraries for visitors based on data analysis and user input. This approach aims to predict and meet individual preferences, redefining engagement and outreach strategies in cultural settings.